2014
DOI: 10.2460/ajvr.75.3.301
|View full text |Cite
|
Sign up to set email alerts
|

Effect of body position on intra-abdominal pressures and abdominal perfusion pressures measured at three sites in horses anesthetized with short-term total intravenous anesthesia

Abstract: Body position affected IAP and APP in healthy anesthetized horses. These effects should be considered when developing IAP acquisition methods for use in horses with abdominal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 33 publications
0
15
1
Order By: Relevance
“…16 Acquisition of IAP measurement in the present study was done Acute abdominal pain in the horse is the most common reason that horses present to a tertiary care facility on emergency. 12 IAH has been recently investigated in the healthy horse, 5,6,11 19 For the purpose of this study, the conventional approach using the mean + 2 SDs was used to determine a ventral IAP cutoff of 32 mm Hg. The drawback of the 95% CI (mean ± 2SD) method is that the upper limit found for negative (healthy) subjects may not coincide with the lower limit found for positive (diseased) cases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…16 Acquisition of IAP measurement in the present study was done Acute abdominal pain in the horse is the most common reason that horses present to a tertiary care facility on emergency. 12 IAH has been recently investigated in the healthy horse, 5,6,11 19 For the purpose of this study, the conventional approach using the mean + 2 SDs was used to determine a ventral IAP cutoff of 32 mm Hg. The drawback of the 95% CI (mean ± 2SD) method is that the upper limit found for negative (healthy) subjects may not coincide with the lower limit found for positive (diseased) cases.…”
Section: Discussionmentioning
confidence: 99%
“…6 Previous reports in horses have indicated that direct intraperitoneal cannulation is the gold standard method for direct measurement of IAP in the horse, with proposed sampling locations including the right flank, left flank, and ventral abdomen. 5,6,11 Colic represents the most common reason that horses present to tertiary care facilities on emergency, and it accounts for 31.2%…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the AC and A25 treatment conditions, all IAP measurements and blood samples were obtained with the dogs positioned in dorsal recumbency during anesthesia. Body position has been shown to affect IAP in both human and veterinary medicine . Although the optimal position for measuring IAP in dogs has not been determined (many studies use the lateral position in dogs, but the dorsal position in people and the sternal position in cats seems to be ideal), standing has not been evaluated and measurements in this position might not be accurate.…”
Section: Discussionmentioning
confidence: 99%
“…Body position has been shown to affect IAP in both human and veterinary medicine. 32,33 Although the optimal position for measuring IAP in dogs has not been determined (many studies use the lateral position in dogs, 2,7,9,10 but the dorsal position in people 1 and the sternal position in cats 11 seems to be ideal), standing has not been evaluated and measurements in this position might not be accurate.…”
Section: Discussionmentioning
confidence: 99%